Self check in public libraries : a case study of Ang Mo Kio Community Library - Wee, Jane Bee Pheng. (2009)
This dissertation is a case study of the implementation of self service in borrowing books by public library users, using the 3M self check machines, in Ang Mo Kio Community Library in 1997. It describes the impact of using the self check-out machines on the users, staff and management, and will serve as a case study for other public libraries which intend to install the machines in the near future.